Lakas sambayanan People power - Montano, Cesar; Apostol, Eugenia D.; Arroyo, Felicitas A.; Nolasco, Butch; Lacaba, Pete.; Founations of Worldwide People Power (Pasig City Foundations for Worldwide People Power, 2002)
A video documentary on the history of People Power in the Philippines.
First broadcast in ABS-CBN Broadcasting Corp. "Lakas Sambayanan" in February 2002 as part of that network's Edsa People Power I commemoration.
Executive producers, Eugenia D. Apostol and Felicitas A. Arroyo.
Narrator, Cesar Montano.
With English subtitles.
Keywords: Philippines -- History -- Revolution, 1986.; Philippines -- Politics and government -- 1986-.